2019
DOI: 10.3846/jcem.2019.7551
|View full text |Cite
|
Sign up to set email alerts
|

A Decision Support Model for Civil Engineering Projects Based on Multi-Criteria and Various Data

Abstract: This paper develops a model, introduced in software, namely Multi-Criteria Decision-Making Model (MCDMM). The model helps decision makers selecting the most suitable alternative based on the customer requirements and preferences. Analytic Hierarchy Process (AHP) and Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (Fuzzy TOPSIS) form a package that covers most available data types in construction projects. In MCDMM, AHP produces criteria relative weights according to their influence on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The increasing popularity of this method relies on its transparency along the decision-making process and its adequacy to represent the rationale of human thinking. In addition, TOPSIS is a highly flexible method that allows for a comprehensive accommodation to the ever more used fuzzy (Issa et al, 2019;Polat et al, 2017) or neutrosophic (Navarro et al, 2019b) environments, without prejudicing its simplicity of use.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…The increasing popularity of this method relies on its transparency along the decision-making process and its adequacy to represent the rationale of human thinking. In addition, TOPSIS is a highly flexible method that allows for a comprehensive accommodation to the ever more used fuzzy (Issa et al, 2019;Polat et al, 2017) or neutrosophic (Navarro et al, 2019b) environments, without prejudicing its simplicity of use.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Jang et al (2018) assessed the green technologies related to urban infrastructure early in the project life cycle, and the evaluation criteria are the additional construction fee, initial construction fee, utilization rate of reducing construction equipment, utilization rate of recycled materials, utilization rate of eco-friendly construction materials, decreased rate of emissions, success factor of a construction project, and level of human capital. Issa et al (2019) selected the best surveying technique for solar energy projects and the identified five criteria are saving in costs, ease of use, rate of capture, applicability, and quality of data.…”
Section: Classification Of Multiple Criteria Decision Making Problems In Civil Engineeringmentioning
confidence: 99%
“…From the scope of civil engineering, we can see that civil engineering involves a variety of decision-making problems. As Issa et al (2019) pointed out, multiple criteria 1 https://baike.baidu.com/item/%E5%9C%9F%E6%9C%A8%E5 %B7%A5%E7%A8%8B/389380?fr=aladdin decision making (MCDM) problems in the field of civil engineering are complicated due to the existence of a large number of evaluation criteria and the nature of conflicting among different criteria, such as the conflict between high quality and low cost. MCDM methods are found to be useful tools to solve the decision-making problems in the field of civil engineering (Abdel-malak et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Fuzzy logic can address indefinite datasets, including data featuring non-statistical uncertainties. In addition, the main benefit of fuzzy set theory compared to other methods is its capability to work with linguistics [23]. For these reasons, fuzzy sets can be used to qualify the linguistic variables that represent the characteristics of a certain project [24].…”
Section: Developing the Proposed Risk Analysis Model (Ramgeb)mentioning
confidence: 99%